2010
DOI: 10.1525/mp.2010.27.4.251
|View full text |Cite
|
Sign up to set email alerts
|

Autism, Music, and the Therapeutic Potential of Music in Alexithymia

Abstract: IT HAS BEEN ARGUED, IN VIEW OF THE SOCIALevolutionary origins of music and the social deficits found in autism, that individuals with autism will be emotionally unresponsive to music. However, a recent study of high-functioning adults with autism has shown that they appear to have a range of responses to music similar to typically developing people, including the deliberate use of music for mood management. In examining why these responses appear unaffected in autism, we explore possible mechanisms for musical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 53 publications
3
33
0
1
Order By: Relevance
“…In common with the above studies, it has been demonstrated that alexithymia and not autism predicts the ability to recognise emotion from both facial and vocal stimuli (Cook, Brewer, Shah, & Bird, 2013;Heaton et al, 2012;Jones et al, 2011). These results strongly support the role of associative learning in linking awareness of one's own emotional states to recognition of those states in another, as highlighted by Quattrocki and Friston (see also Allen & Heaton, 2010;Bird & Viding, 2014;Gergely & Watson, 1996;. All of these studies adopted a 'four group' design, crossing the presence/absence of autism and alexithymia, and so could specifically separate out the effects of autism and alexithymia.…”
Section: Alexithymia But Not Autismsupporting
confidence: 83%
“…In common with the above studies, it has been demonstrated that alexithymia and not autism predicts the ability to recognise emotion from both facial and vocal stimuli (Cook, Brewer, Shah, & Bird, 2013;Heaton et al, 2012;Jones et al, 2011). These results strongly support the role of associative learning in linking awareness of one's own emotional states to recognition of those states in another, as highlighted by Quattrocki and Friston (see also Allen & Heaton, 2010;Bird & Viding, 2014;Gergely & Watson, 1996;. All of these studies adopted a 'four group' design, crossing the presence/absence of autism and alexithymia, and so could specifically separate out the effects of autism and alexithymia.…”
Section: Alexithymia But Not Autismsupporting
confidence: 83%
“…The sources of learning by which such links may be formed have been delineated elsewhere (e.g. Heyes, 2001;Allen and Heaton, 2010;Heyes, 2010a,b) and include: direct self-observation (the infant feels happy and laughs, enabling the affective state of being happy to be associated with the sound of a laugh), mirror self-observation (the infant is able to observe their own reflection while producing an emotional facial expression -thus associating the internal affective state which caused their emotional facial expression to be associated with a perceptual representation of that emotion), synchronous action (both the infant and caregiver respond with fear to a loud noise, enabling the internal fearful emotion to be associated with a perceptual representation of fear), acquired equivalence experience (when both the internal affective state and a perceptual representation of that state in another are both associated with a common third representation, such as a sound like "Yuck" for example), and being imitated by another, typically the primary caregiver (being imitated provides correlated experience of being in an affective state while perceiving the emotional expression corresponding to that state). All of these kinds of experience will result in perception of emotion in another activating in oneself the corresponding affective state via the learned links between perceptual and affective representations of emotion.…”
Section: The Self To Other Model Of Empathy (Some)mentioning
confidence: 99%
“…However, the directionality of this association between verbal abilities and emotion recognition is unknown. Allen & Heaton (2010) suggest that the (in)ability to describe emotions in music may relate to alexithymia. It would be interesting to compare how individual differences in recognizing or feeling musical emotions compare with emotion identification in other domains.…”
Section: Music and Emotionmentioning
confidence: 99%
“…However, as discussed by Allen and Heaton (2010), the shortcomings of previous research should not lead one to disregard this potentially useful tool when designing interventions. The strengths evident in individuals with ASDs for pitch perception and basic emotion recognition in music suggest that music could aid the development of social and communication skills.…”
Section: Asd and Music Therapymentioning
confidence: 99%